Review on Eco-friendly Green Synthesis Methods of Tungsten OxideNanoparticles - Al-Obaidi, Noor Sabah; Al-Mahdawi, Anfal Salam; Abd, Ahmed N.; Ahmed , Ahmed A. (ASJ - Academic Science Journal, 2025)
Synthesis of tungsten oxide nanoparticles by alternative method has been use of environmentally friendly green methods that involve natural materials like plants, bacteria, fungi, solvothermal, microwave-assisted, biosynthesis, sonochemical, polysaccharides, seaweed, plant-derived materials, biodegradable polymers, and algae. using effective green chemistry to create nanoparticles has sparked a lot of attention lately due to its environmental friendly, simplicity, affordability, and clean technology. It also doesn't use any dangerous chemicals and produces no impurities or wastes. Plant extracts have garnered the greatest attention among these bio-entities due to their special natural qualities that enable them in a single production step to stabilize and decrease metal nanoparticles. The changes and future prospects of green synthesis methods using plant extracts, solvothermal, microwave-assisted, biosynthesis, and sonochemical processes for tungsten oxide nanoparticles are reviewed in this paper.